2011
DOI: 10.1523/jneurosci.4039-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Intracellular ATP Influences Synaptic Plasticity in Area CA1 of Rat Hippocampus via Metabolism to Adenosine and Activity-Dependent Activation of Adenosine A1Receptors

Abstract: The extent to which brain slices reflect the energetic status of the in vivo brain has been a subject of debate. We addressed this issue to investigate the recovery of energetic parameters and adenine nucleotides in rat hippocampal slices and the influence this has on synaptic transmission and plasticity. We show that, although adenine nucleotide levels recover appreciably within 10 min of incubation, it takes 3 h for a full recovery of the energy charge (to Ն0.93) and that incubation of brain slices at 34°C r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
89
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(100 citation statements)
references
References 81 publications
10
89
1
Order By: Relevance
“…We found that, despite the attenuation in ATP levels, EC was close to values recorded in vivo (typically ~0.95) [23,77]. This suggests that a new metabolic equilibrium had been achieved amongst the remaining adenine nucleotides.…”
Section: Atp Loss and Replenishment In Brain Tissue: Lessons From Thesupporting
confidence: 75%
See 1 more Smart Citation
“…We found that, despite the attenuation in ATP levels, EC was close to values recorded in vivo (typically ~0.95) [23,77]. This suggests that a new metabolic equilibrium had been achieved amongst the remaining adenine nucleotides.…”
Section: Atp Loss and Replenishment In Brain Tissue: Lessons From Thesupporting
confidence: 75%
“…2) [23]. We additionally examined the energy charge (EC) [76] of the slices, which conveys the energetic state of a cell and is given by the following equation:…”
Section: Atp Loss and Replenishment In Brain Tissue: Lessons From Thementioning
confidence: 99%
“…Since their inception, brain slices have been criticised for their ATP levels, which are typically 50% lower than values observed in vivo. We have recently addressed this issue [70] to investigate whether the reduction in ATP reflects loss of salvageable metabolites during brain slice preparation, analogous to injury to the intact brain in vivo, or whether this reflects a fundamental metabolic handicap that brain slices suffer from.…”
Section: Purine Salvagementioning
confidence: 99%
“…6), which raised the threshold for the induction of long-term potentiation. This release seemed to be independent of prior release of ATP as it was insensitive to the ecto-ATPase inhibitor POM1 [71], but sensitive to a combination of equilibrative nucleoside transporters (ENTs) inhibitors [70]. In these experiments, sensors were invaluable as they allowed the kinetics of enhanced adenosine release to be established, which would not have been possible through the use of receptor antagonists.…”
Section: Purine Salvagementioning
confidence: 99%
See 1 more Smart Citation